Transition from IPv4 to IPv6 Network in IoT Security Based Upon Transition Methods - Ms. Shilpa B. Sarvaiya; Dr. D. N. Satange (International Journal on Orange Technologies, 2021)
While deployments of IPv6 networks have increased over recent years, especially in IoT Paradigm. Today there are two types of internet protocol versions that are currently working in the global internet to transfer data from one electronic device to another.IPv4 which consists of 32 bits long addresses and IPv6 which consists of 128bits long addresses which is more effective as it can handle billions of devices and can assign each device different IP address. This paper will present an overview of the main migration technologies that can be used to transition from an IPv4 network to an IPv6 network, this paper will also research on finding and comparing the effects of IPv6 transition methods such as Dual Stack, Tunneling and Network Address Translation-Protocol Translation will be compared on variant parameters to find the best performing transition method in IoT Network in terms of security.